(untitled) (Olhar de Professor, 2024)
Science challenges the relevance of school geometry in its treatment of space. Therefore, the research discusses the incorporation of non-Euclidean geometries in the initial and continuing education of mathematics teachers. Hence, this literature review aims to synthesize and describe, in a broad and current range, the recent state of research in educational mathematics on these geometries in teacher education. To do this, we configured a method in three moments: the search, evaluation, selection, and organization of the sources found and reading, analyzing, and writing results. The results highlight a regional and temporal interest that prioritizes teaching practice. Furthermore, a deficit and prescriptive perspective of teachers’ knowledge and a minority perspective of the teacher as a subject of knowledge are recognized. We conclude with the need for research on various phenomena, including Euclidean generalizations.